Comparative transcriptomic and lipidomic analyses indicate that cold stress enhanced the production of the long C18–C22 polyunsaturated fatty acids in Aurantiochytrium sp. - Song, Yingjie; Hu, Zhangli; Xiong, Zheng; Li, Shuangfei; Liu, Wei; Tian, Tian; Yang, Xuewei (Frontiers in Microbiology, 2022)
Aurantiochytrium sp. belonging to Thraustochytrids are known for their capacity to produce long-chain polyunsaturated fatty acids (PUFAs). However, effects of cold stress accompanied with staged-temperature control on the fatty acid metabolism in Aurantiochytrium sp. were rarely studied. In this study, cold stress (15 °C, 5 °C) followed with the cell growth temperature (25 °C) was applied for Aurantiochytrium sp., with the physiological responses (morphology, growth, fatty acid profiling) and gene expression (FA synthesis, lipid metabolism, and regulatory processes) changes further explored. Results showed that there is a significant change for the lipid types observed under 5 °C (251 species) and 15 °C (97 species) treatment. The 5 °C treatment was benefit for the C18–C22 PUFAs with the yield of DHA increased up to 1.25 times more. After incubation at 15 °C, the accumulation of eicosadienoic acid (EA, 20:2) was increased to 2.00-fold. The transcriptomic results revealed that key enzymes involved in fatty acid synthase (FAS) and polyketide synthase (PKS) pathways were upregulated to increase the accumulation of FAs under low-temperature treatment. With upregulation of 3-ketoacyl-CoA synthase (2.44-fold), ketoreductase (2.50-fold), and dTDP-glucose 4,6-Dehydratase (rfbB) (2.31-fold) involved in PKS pathway, the accumulation of DHA was enhanced under 5 °C incubation. While, fatty acid synthase (FAS) and fatty elongase 3 (ELO) involved in the FAS pathway were upregulated (1.55-fold and 2.45-fold, respectively) to accumulate PUFAs under 15 °C incubation. Additionally, glycerol-3-phosphate acyltransferase (GPAT), lysophospholipid acyltransferase (LPAT), phosphatidic acid phosphatase (PAP), phosphatidylserine synthase (PSS), and phosphatidylserine decarboxylase (PSD) involved in glycerophospholipid biosynthesis were upregulated under 5 °C incubation to increase the accumulation of PA, PC, PE, PG, and PI. However, glycolysis and the TCA cycle were inhibited under 5 °C. This study contributes to the understanding of cold stress-enhancing PUFAs, especially DHA synthesis in Aurantiochytrium sp., and provides a better understanding of the functions of key genes for future genetic engineering.